Low-Code Quality Metrics for Agile Software Development - Domingues Filho, Renato Cavalcanti; Silva, Mario J.; Marinho, Marcelo Luiz Monteiro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
We present a quality metrics monitoring and analysis platform, which has been developed to support the main goal of delivering customer value at competitive costs without sacrificing quality in the context of fast digital transformation using a low-code platform and agile development methods. The quality platform collects project data and enables the automatic computation of metrics tailored to our software process that development teams can use for self-assessment. Since introducing our platform two years ago, our teams have been using it constantly, demonstrating its effectiveness and importance for our software development process.